Measurement and Analysis of the Noise Level in Selected Zones of Bus Stops in the City of Radom - Tomasz Perzyński (Communications - Scientific letters of the University of Zilina, 2021)
The noise from means of transport is one of the main factors of environmental noise pollution and is one of the factors having an effect on human health. The article presents the problem of noise emitted by urban means of transport. The work focuses on analysis of the acoustic climate in the bus stop zone. In order to estimate the noise level, research was conducted in selected points in one of the Polish cities - Radom. The obtained results allowed assessment of the impact of transport on the noise level in the area of selected bus stops.